2020
DOI: 10.1016/j.jep.2020.112735
|View full text |Cite
|
Sign up to set email alerts
|

Viral hepatitis in the Peruvian Amazon: Ethnomedical context and phytomedical resource

Abstract: Ethnopharmacological relevance An extensive ethnopharmacological survey was carried out in the Peruvian Amazonian district of Loreto with informants of various cultural origins from the surroundings of Iquitos (capital city of Loreto) and from 15 isolated riverine Quechua communities of the Pastaza River. A close attention was paid to the medical context and plant therapy, leading to the selection of 35 plant species (45 extracts). The extracts were tested for antiviral activity against HCV with counting of Hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 78 publications
(62 reference statements)
0
15
0
Order By: Relevance
“…Etnomedicine explains local wisdom that can be used in medicine and its scientific explanation is carried out in research-based learning in the laboratory. The manufacture of traditional medicine from local plants contributes better to the local medical system (Roumy et al 2020). From this research, it was found that local plants are efficacious for treating hepatitis.…”
Section: Discussionmentioning
confidence: 82%
“…Etnomedicine explains local wisdom that can be used in medicine and its scientific explanation is carried out in research-based learning in the laboratory. The manufacture of traditional medicine from local plants contributes better to the local medical system (Roumy et al 2020). From this research, it was found that local plants are efficacious for treating hepatitis.…”
Section: Discussionmentioning
confidence: 82%
“…Compounds from Peruvian medicinal plants have been evaluated for their antidiabetic [93], anticancer [94], antiviral [95], antibiotic [96], and antiparasitic activities [97]; however, most of the studies in the literature were in vitro performed over plants extracts, and little information about the potential of single compounds on these activities is described, while these promising results can be explained by synergistic interaction or multi-factorial effects between compounds present in the plant extracts studied [98]. While pharmacodynamic synergy involves multiple substances acting on various receptor targets to enhance the overall therapeutic effect, and pharmacokinetic synergy involves substances with little to no activity helping the main active principle to reach the target by improving bioavailability or by reducing metabolism and excretion, this type of assay can hide the true potential of single molecules activity between different constituents of plant extracts.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, O. basilicum and Bidens pilosa were reportedly used to treat hepatitis in Taiwan although B. pilosa [17] was used for the treatment of COVID-19 in the present study. Likewise, C. papaya and Jatropha curcas were reportedly used to treat hepatitis and hepatic disease in Peruvian Amazon [18] .…”
Section: Discussionmentioning
confidence: 99%